Tourism / Principles and Practise - Cooper, Chris; Fletcher John; Wanhill Stephen (Longman, 1993)
The text presents a holistic approach to the subject and is structured around the 4 key elements of tourism - demand, destination, the industry and government organizations, and marketing. Preface, An Introduction to Tourism, Demand for Tourism, Concepts and Definitions of Demand for Tourism, Consumer Behavior and Tourism Demand, Determinants of Tourism Demand, Measuring the Demand for Tourism, Patterns of Demand, The Tourist Destination, Patterns and Characteristics of the Supply of Tourism, Carrying Capacity and the Sociocultural and Environmental Impacts of Tourism, The Economic Impact of Tourism, Tourism and Development Planning, The Tourism Industry and Government Organizations, Introduction, Government Organizations, Accommodation, Transportation, Intermediaries, Attractions, Marketing for Tourism, Marketing for Tourism - The Historical Roots, Marketing Management, Marketing Planning, Marketing Mix, The Future of Tourism, Compendium of Tourism Texts and Journals, Index.